2012
DOI: 10.47893/ijatce.2012.1048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water-to-Geopolymer Binder Ratio on the Production of Fly Ash Based Geopolymer Concrete

Abstract: Geopolymer is a new invention in the world of concrete in which cement is totally replaced by pozzolanic material that is rich in silica and alumina like fly ash and activated by alkaline liquids to act as a binder in the concrete. Experimental investigation has been carried out to study the effect of water-to-geopolymer binder ratio on workability in terms of flow and compressive strength tested after heat curing in oven at 900C for 8 hours duration. Activated liquid to fly ash ratio of 0.35 by mass was maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 5 publications
1
7
0
1
Order By: Relevance
“…It implied that the tested cubes compressive strength of free cement mortars was inversely proportional with the water to binder ratio (H2O:B) which was similar to that of water to cement ratio in cement mortar. This finding was agree with the previous reports by Sathonsaowaphak et al(31), and Patankar et al(32). Moreover, the loss of compressive strength with increasing alkaline solution content implied the quantity of water present in the mix was much higher than the required as also confirmed by Chi(33).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…It implied that the tested cubes compressive strength of free cement mortars was inversely proportional with the water to binder ratio (H2O:B) which was similar to that of water to cement ratio in cement mortar. This finding was agree with the previous reports by Sathonsaowaphak et al(31), and Patankar et al(32). Moreover, the loss of compressive strength with increasing alkaline solution content implied the quantity of water present in the mix was much higher than the required as also confirmed by Chi(33).…”
supporting
confidence: 93%
“…On other hand, several researcher reported that the flow diameter increases almost linearly with the increase in percentage of H2O to CaO, H2O to SiO2 and H2O to Al2O3 (28-30). (32). Moreover, the loss of compressive strength with increasing alkaline solution content implied the quantity of water present in the mix was much higher than the required as also confirmed by Chi (33).…”
Section: Resultsmentioning
confidence: 65%
“…Additionally, the CS of GPC decreases as the percentage of water increases [6]. The performance of FA based GPC has been studied by Patankar et al [15] in relation to the impact of the liquid to binder (l/b) ratio. They found that as the ratio of l/b was raised, the compressive strength of GPC decreased.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional Portland cement is completely replaced with an aluminosilicate material activated by a strongly alkaline solution as a binder. (Patankar et al, 2013). Metakaolin, fly ash, red mud, agricultural waste, and mine waste are natural and industrial products used to make geopolymer binders (Slaty et al, 2013).…”
Section: Introductionmentioning
confidence: 99%